Top secret tales of World War II - Breuer, William B. (John Wiley & Sons, 2000)
Critical Acclaim for TOP SECRET TALES of World War II "A book for rainy days and long solitary nights by the fire. If there were a genre for cozy nonfiction, this would be the template.